Analisis Pertumbuhan Jagung akibat Pemberian Gambut dan Pemupukan Fosfat pada Tanah Mineral Masam Podzolik (Ultisol) - Bukhari Bukhari (Jurnal Agrista, 2006)
Corn Growth Analysis with Peat Application and Posfat Fertilization on Mineral Acid Podzolik Soil (Ultisol)ABSTRACT. The experiment to improve mineral acid soil productivity in Aceh that is potential to plantation. This experiment was conducted during the month of February until Mei 2006. It studied the effect of peat application, phosphate fertilization and the effect of the interaction. They were consist of sixteen combination of treatment with fourty eight plots. The experimental design was in randomized completely block design, there were two factors treatment. e.i. four level of peat namely; no pead, 10 ton, 20 ton, and 30 ton ha-1. The result shows that in general the application of peat and phosphate fertilization with different level were able to improve significantly the corn growth e.i.: crop growth rate, relative growth rate, net assimilation rate, and leaf area biomassa ratio, but they interaction were not significantly on 4 – 8 weeks periode. The interaction were significantly on 8 weeks to harvest periode however the two single factor show nonsignificantly. The interaction between pead application of 2 ton ha-1 and 100 ton ha-1 posfat fertilization gave a better result.